CS-09 PROPOSAL OF A NEW CLASSIFICATION FOR DETERMINING THERAPEUTIC STRATEGY ACCORDING TO THE PROGRESSION OF OLFACTORY NEUROBLASTOMA. (16th December 2019) - Motegi, Hiroaki; Yamaguchi, Shigeru; Ishi, Yukitomo; Endo, Shogo; Kobayashi, Hiroyuki; Terasaka, Shunsuke; Suzuki, Masanobu; Nakamaru, Yuji; Homma, Akihiro; Houkin, Kiyohiro
Abstract: INTRODUCTION: Olfactory neuroblastoma (ONB) is a rare type of malignancy that infiltrates and propagates from the nasal cavity to the anterior skull base and into the cranium. Various treatment strategies have been used at different institutions and time of treatment. Although the staging system proposed by Kadish is commonly adopted has not proven useful for predicting prognosis or choosing among treatment strategies. Factors to be considered have increased accordingly, for example, whether to perform ESS alone or in combination with craniotomy, whether to try preserving the olfactory sense and whether to use neoadjuvant chemotherapy. In this study, we reviewed ONB cases treated at our institution to propose a new classification system to help determine treatment strategies. METHODS: Thirty-four patients treated at Hokkaido University were included. Stages of craniocaudal progression were defined as Nasally/Paranasally localized (NP), Frontal Base progression (FB), and Brain invasion (BI). Stages of lateral progression were defined as Midline (M) or Lateral extension (L), and Unilateral (U) or Bilateral (B). RESULTS: Between 2008 and 2016, patients at the BI stage were proactively treated with neoadjuvant chemotherapy and achieved long-term survival (mean overall survival, 64.2 months). However, no standard way of choosing among treatment options was established. M-stage patients underwent concurrent craniotomy. From 2017 onwards, 5 patients were treated according to the new classification system. All were FB-M cases, including 4 cases of B disease, in which ESS alone followed by radiotherapy was used. One patient in the FB-M-U category underwent unilateral resection and the olfactory sense was preserved. In general, the treatment with ESS alone appeared to be preferred for M disease, and surgery after neoadjuvant chemotherapy was advisable for BI cases. CONCLUSION: The result suggests that the new classification system is helpful to decide the treatment strategy according to the progression of ONB.